ANALYSIS OF STUDENTS' ERROR IN WORKING ON MATHEMATICS PROBLEMS BASED ON THE CIRCULAR MATERIAL BASED ON KASTOLAN THEORY - Rahayu, Sri Lestari; Murtiyasa, Budi (FKIP Universitas Muhammadiyah Tangerang, 2024)
The purpose of this study is to describe the types of student errors in solving HOTS-based circle questions based on kastolan theory, then it will also be explored regarding the factors that cause errors, and the percentage of student errors when solving problems. The method that will be used is descriptive qualitative. The instruments in this study consisted of written tests, interviews, and documentation. Data analysis techniques include data reduction, presenting data, and drawing conclusions. The subjects in this study were 13 students from class VIII A of SMP Negeri 4 Randublatung in semester 2 of the 2022/2023 academic year. Then interviews will be conducted by taking 3 samples of student answers grouped based on types of conceptual, procedural, and technical errors. The results showed that the most dominant errors occurred in technical errors where errors were made in the counting process with a percentage of 69.23%. Student procedural errors were made due to the incompatibility of the steps in solving the questions which resulted in wrong answers, with a percentage of 53.84%. Students' conceptual errors were made because students misinterpreted concepts and incorrectly determined the problem solving formula, with a percentage of 46.15%. Factors that cause students to make mistakes in solving HOTS-based questions are: students are not careful in the process of calculating ranks, use formulas that do not meet the prerequisites of the formula, and incompatibility of steps in solving problems.Keywords: Error Analysis, Cricles, HOTS Type Questions, Kastolan Theory